PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI KEAMANAN, PERSEPSI MANFAAT TERHADAP MINAT PENGGUNAAN E-WALLET PADA MAHASISWA AKUNTANSI DI KOTA BATAM - Kie, Daniel; Indonesia, Indonesia (LPPM Universitas Putera Batam, 2024)
ABSTRACT This research aims to investigate the factors influencing the usage intention of E-wallets among university students, focusing on the perceptions of ease of use, security, and benefits. The research population includes students from six higher education institutions: Universitas Internasional Batam, Universitas Riau Kepulauan, Universitas Universal, Universitas Batam, Politeknik Negeri Batam, and Universitas Ibnu Sina, with a total population of 1,758 students. The research sample consists of 330 students. Data collection was conducted through the distribution of online questionnaires to students from these institutions via Google Forms. The questionnaire items were measured using Likert scales, and data analysis was performed using the IBM SPSS Statistics Version 25 software. The tests conducted in this study include descriptive statistical analysis, data quality assessment involving validity and reliability tests, classical assumption checks including tests for normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, as well as hypothesis testing such as partial and simultaneous tests. Additionally, a coefficient of determination test was conducted to determine how much variability in the dependent variable could be explained by the independent variables in the research model. The results of the testing indicate that perceptions of ease of use and perceived benefits significantly influence the usage intention of E-wallets in Batam city. However, the perception of security does not significantly affect the usage intention of E-wallets.